2012
DOI: 10.1002/lary.22471
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of risk factors for spasmodic dysphonia: A comparison with other voice disorders

Abstract: SD is likely multifactorial and associated with several endogenous and exogenous factors. Certain viral exposures, voice use patterns, and familial neurological conditions may contribute to the onset of SD later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Previously published data report similar age of onset, female gender predominance, environmental risk factors and response to treatment. 1,2,29,30 In addition, we restricted the evaluation to GAG deletions in the coding region of TOR1A. Other disease-causing mutations in this gene have been described but appear exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data report similar age of onset, female gender predominance, environmental risk factors and response to treatment. 1,2,29,30 In addition, we restricted the evaluation to GAG deletions in the coding region of TOR1A. Other disease-causing mutations in this gene have been described but appear exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with focal LD often have a history of a sore throat,35 and one study comparing 150 patients with LD and 136 patients with other voice disorders (excluding vocal tremor) confirmed the observation (see Table 1 for details on the strength of the association) 26. However, the authors found no relationship between the number of sore throats per year and dystonia risk.…”
Section: Environmental Factors and Primary Late-onset Dystoniamentioning
confidence: 90%
“…A study evaluating a large number of variables in 104 consecutive patients with writer's cramp (WC) and matched controls found a significant positive association between head trauma with loss of consciousness and WC (OR, 3.5; 95% CI 1.0–15.7) 25. Similarly, a study assessing several possible risk factors in 150 patients with laryngeal dystonia (LD) and 136 control subjects with other voice disorders observed a significant inverse association with head trauma and loss of consciousness 26. Hall et al did not find any association between head trauma and BSP, which may have been due to insufficient study power 27.…”
Section: Environmental Factors and Primary Late-onset Dystoniamentioning
confidence: 98%
See 1 more Smart Citation
“…3 Little is known about the natural history of SD, making prognostication difficult. 4 There is no definitive treatment of this chronic disease; surgical and chemical denervation of the affected muscles can temporarily palliate symptoms but do not restore baseline function. Although once considered a psychogenic phenomenon, SD's resistance to speech therapy and psychiatric treatment, which can be effective for muscle tension (muscle tension dysphonia [MTD]), true psychogenic dysphonias, and other dysphonias, suggests otherwise.…”
Section: Introductionmentioning
confidence: 99%